Effectiveness of the Digital Population Identity (IKD) Program at the Population and Civil Registration Office of Bogor Regency - Therasari, Anita; Salbiah, Euis; Apriliyani, Neng Virly (Universitas Negeri Gorontalo, 2025)
The implementation of the Digital Population Identity (IKD) is one of the government’s efforts to digitize public services, particularly in the area of civil registration. This study aims to evaluate the effectiveness of the IKD program conducted by the Department of Population and Civil Registration (Disdukcapil) of Bogor Regency. The research uses a descriptive quantitative approach to gain a statistical picture of public perceptions of the program. Data were collected from 100 respondents through a structured questionnaire, supported by interviews with key officers at Disdukcapil. The effectiveness of the IKD program was measured using five dimensions proposed by Sutrisno (2010): program understanding, target accuracy, timeliness, goal achievement, and actual change. The results of this study indicate that the IKD program in Bogor Regency is considered effective, with an overall average score of 3.83, categorized as